2010
DOI: 10.1016/j.neuroscience.2009.12.027
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive analysis of the effect of DSP4 on the locus coeruleus noradrenergic system in the rat

Abstract: Degeneration of the noradrenergic neurons in the locus coeruleus (LC) is a major component of Alzheimer's (AD) and Parkinson's disease (PD), but the consequence of noradrenergic neuronal loss has different effects on the surviving neurons in the two disorders. Therefore, understanding the consequence of noradrenergic neuronal loss is important in determining the role of this neurotransmitter in these neurodegenerative disorders. The goal of the study was to determine if the neurotoxin N-(2-chloroethyl)-N-ethyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
79
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(88 citation statements)
references
References 79 publications
8
79
1
Order By: Relevance
“…Noradrenaline depletion in the rodent by N-(2-chloroethyl) -N-ethyl-2-bromobenzylamine (DSP-4) is an approach commonly used to model human neuropsychiatric disorders in rodents [54]. Although there are yet no studies with DPS-4 and DBS, one study using only DSP-4 shows that although administration of DSP-4 to rats does not result in any obvious behavioral changes, animals that received DSP-4 initially gained weight at a slower rate than control animals [19,43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Noradrenaline depletion in the rodent by N-(2-chloroethyl) -N-ethyl-2-bromobenzylamine (DSP-4) is an approach commonly used to model human neuropsychiatric disorders in rodents [54]. Although there are yet no studies with DPS-4 and DBS, one study using only DSP-4 shows that although administration of DSP-4 to rats does not result in any obvious behavioral changes, animals that received DSP-4 initially gained weight at a slower rate than control animals [19,43].…”
Section: Discussionmentioning
confidence: 99%
“…Although there are yet no studies with DPS-4 and DBS, one study using only DSP-4 shows that although administration of DSP-4 to rats does not result in any obvious behavioral changes, animals that received DSP-4 initially gained weight at a slower rate than control animals [19,43]. However, a comprehensive analysis of the effect of DSP-4 on the locus coeruleus noradrenergic system in the rat has shown that DSP-4 does not reduce locus coeruleus noradrenergic number or function, suggesting that DSP-4 is not an appropriate rat model to study the functional effect of noradrenergic neuronal loss in PD [54].…”
Section: Discussionmentioning
confidence: 99%
“…As indicated earlier, these regions receive sole innervation from the LC (Aston- Jones et al, 1995;Jones & Moore, 1977;Loughlin et al, 1986a, b;Mason & Fibiger, 1970;Moore & Bloom, 1979;Olsen & Fuxe, 1971;Ungerstedt, 1971;Waterhouse et al, 1983) so the original hypothesis was that DSP4 affected only LC neurons. NET binding sites are also reduced in specific forebrain regions, indicating a loss of innervation from the LC (Cheetham et al, 1996;Szot et al, 2010). The hypothesis that DSP4 was a neurotoxin was supported by TH-IR which demonstrated a gradual loss of LC noradrenergic neurons after by DSP4 administration .…”
Section: Reduced Lc Function Enhances Susceptibility Of Dopaminergic mentioning
confidence: 93%
“…A) L-DOPA level, B) DA and NE levels and C) DOPAC and DHPG CSF levels in control and PD subjects on L-DOPA treatment. Catecholamine levels were extracted by alumina extraction and analyzed by high performance liquid chromatography (HPLC) as previously described (Szot et al, 2010). Each point represents a single individual catecholamine value for control and PD subjects, with average and standard error means (SEM) illustrated in bars for each catecholamine analyzed.…”
Section: Effect Of L-dopa Treatment On Noradrenergic Systemmentioning
confidence: 99%
See 1 more Smart Citation